Answer:
The solution of the given equation is x = 2.
Step-by-step explanation:
The given linear equation is,
At first, we will eliminate '4' from the LHS by dividing both sides i.e., LHS and RHS by 4 because '4' is present in multiplication with the term containing unknown in LHS.
So, dividing both sides by '4', we get
Our next step will be to eliminate '3' from the LHS that is being subtracted from the term containg unknown variable. For this, we will add '3' on both sides of the above obtained equation.
So, adding '3' on both sides, we get
Now, we will eliminate '2' from the LHS that is in multiplication with the unknown variable 'x'.
For this, we will divide both sides of the above obtained equation by '2'.
So, dividing both sides by '2', we get
CHECKING :
For this, we will substitute x = 2 in the LHS of the given equation and then check whether it is equal to RHS or not.
LHS = 4(2x - 3)
= 4(2 × 2 - 3)
= 4(4 - 3)
= 4 × 1
= 4
= RHS
So, the solution of the given equation is x = 2.
Answer:
see explanation
Step-by-step explanation:
(A) Given
4(2x - 3) = 4 ( divide both sides by 4 )
2x - 3 = 1 ( add 3 to both sides )
2x = 4 ( divide both sides by 2 )
x = 2
(B)
As a check substitute x = 2 into the left side of the equation and if equal to the right side then it is the solution.
4(2(2) - 3) = 4(4 - 3) = 4(1) = 4 = right side
Hence x = 2 is the solution
Solve for f(x) using both 4 and 8:
f(x) = 4+6 = 10
f(x) = 8+6 = 14
Find the difference between the answers:
The difference between the two answers is 14-10 = 4
Find the difference between the interval:
The difference between 4 and 8 is: 8-4 = 4
The rate of change is the change in the answers over the difference in the interval:
The rate of change is 4/4 = 1
Answer:
The Average rate of change for f(x) = x+6 over the interval (4,8) is 1
Solution:
We define the Average rate of function f(x) over the interval (a, b) as
--- eqn 1
From question, given that
f(x) =x+6 --- eqn 2
The interval is (4,8) .hence we say a = 4 and b = 8
The average rate of change for f(x) = x + 6 is given by using eqn 1
--- eqn 3
Where, by using eqn 2 , we get f(8) = 8+6 =14 and f(4) = 4+6 =10
Such that the required value would be f(8)-f(4) = 14-10 = 4
By substituting the values of f(8) and f(4) in eqn 3 ,the average rate of change for the given expression is
Hence the Average rate of change for f(x) = x+6 over the interval (4,8) is 1
Answer:
For x: We subtract the exponents,
this way. 0 - 2 = -2
For y: We subtract the exponents,
this way. -3 - -1 = -2
x -² y -²